Method of calculation of gravity type washing equipment - Tarasenko, D. (Запоріжжя : ТДАТУ, 2025)
To remove products of corrosion, grease residues, asphalt-resin deposits from parts during machine repair, as well as burrs from the surfaces of newly manufactured parts, it is effective to use cleaning methods based on tumbling techniques. Small parts (valve rocker arms, pushers, valve spring seats, valve springs, etc.) and normals (bolts, nuts, studs) placed in a basket are poorly cleaned in jet installations, and therefore it is advisable to use the abrasive cleaning method for their cleaning.The essence of abrasive cleaning is that the surfaces of parts are freed from contaminants due to mutual friction between themselves and the walls of a rotating drum, dynamic interaction with the abrasive, which has a large reserve of kinetic energy. This energy is spent on cutting contaminants in the form of small chips and on their grinding.
Keywords: abrasive fillers; gravity cleaning